2020
DOI: 10.3390/biology9120465
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Selenite and Selenate in the Regulation of Growth and Physiological Parameters of Nickel-Exposed Lettuce

Abstract: Nickel is an essential plant micronutrient; however, even at low concentrations, it may be phytotoxic. Selenium is a beneficial element with an alleviating effect that has been confirmed in the case of many abiotic stresses, including metal toxicity. The aim of this study is to assess the effect of two forms of Se (Se(IV) or Se(VI)) on the phytotoxicity, accumulation, and translocation of Ni in lettuce. Nickel causes a reduction in lettuce growth and vitality of roots, probably through increased lipid peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Based on Dai et al, Se 5 is effective in increasing As accumulation by P. vittata . However, lower Se concentrations have been used in literature, so we used both Se 1.25 and Se 5 in this study. Furthermore, Se is effective in enhancing As accumulation in P. vittata under 13–133 μM As, , so we selected 50 μM As.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Dai et al, Se 5 is effective in increasing As accumulation by P. vittata . However, lower Se concentrations have been used in literature, so we used both Se 1.25 and Se 5 in this study. Furthermore, Se is effective in enhancing As accumulation in P. vittata under 13–133 μM As, , so we selected 50 μM As.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggested that the application of exogenous amino acids, including histidine, glycine, and glutamine, can enhance the symplastic-to-apoplastic Ni ratio in root and promote the translocation of this metal to shoots. It is probable that Se ions or Se-bound amino acids may similarly contribute to the symplastic uptake and subsequent translocation of Ni, thereby enhancing the plant tolerance to Ni, but more research is required to substantiate this assertion. , Other findings have reported the influence of Se on the accumulation and transport of Cu and Ni. The assimilation of Se by plants has been observed to modify the ionic permeability coefficient within the cell plasma membrane, consequently influencing the uptake of other ions such as micronutrients. , Additionally, it is of great importance to mention that Ni is extremely important for nitrogen (N) metabolism in plants.…”
Section: Resultsmentioning
confidence: 99%
“…It is probable that Se ions or Se-bound amino acids may similarly contribute to the symplastic uptake and subsequent translocation of Ni, thereby enhancing the plant tolerance to Ni, but more research is required to substantiate this assertion. 34,38 Other findings have reported the influence of Se on the accumulation and transport of Cu and Ni. The assimilation of Se by plants has been observed to modify the ionic permeability coefficient within the cell plasma membrane, consequently influencing the uptake of other ions such as micronutrients.…”
Section: Influence Of Se Biofortification On Mineralmentioning
confidence: 99%
“…The growth of high plant is inseparable from oxygen (O 2 ) and reactive oxygen species (ROS) produced in various biological metabolic processes. In general, the generation and removal of ROS in plants maintain a stable dynamic balance under normal growth conditions (Hawrylak-Nowak et al 2018). When plants are subjected to environmental stresses, ROS including superoxide anion radical (O 2 .À ), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (-OH), singlet oxygen ( 1 O 2 ), and lipid peroxidation radical (LOOÁ, ROOÁ) are excessively induced in plants (Feng et al 2013), and this condition leads to membrane lipid peroxidation, destroys the normal structure and function of biological molecules, and causes irreversible oxidative damage to plant cells (Malar et al 2015).…”
Section: Se Promotes Ros Scavengingmentioning
confidence: 99%
“…ramosa Hort.) plants, and reduce the Ni accumulation (Hawrylak‐Nowak & Matraszek‐Gawron 2020). Similar results were also obtained in wheat ( Triticum aestivum L.) planted on Cd‐contaminated soil.…”
Section: Se Repairs Plant Cell Structure and Functionmentioning
confidence: 99%